2006
DOI: 10.1158/1078-0432.ccr-05-2170
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibits Growth of Premalignant and Malignant Mammary Lesions in a Mouse Model of Ductal Carcinoma In situ

Abstract: Purpose: Rapamycin has been shown to have antitumor effects in various tumor models.To study the effect of rapamycin at different stages of breast cancer development, we used two unique mouse models of breast cancer with activated phosphatidylinositol 3-kinase (PI3K) pathway. Met-1 tumors are highly invasive and metastatic, and mammary intraepithelial neoplasiaoutgrowths (MIN-O), a model for human ductal carcinoma in situ, are transplantable premalignant mammary lesions that develop invasive carcinoma with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 34 publications
4
47
0
2
Order By: Relevance
“…HIF-1␣ has been shown to be an excellent correlate of rapamycin response in a transgenic model of prostate neoplasia dependent on activated Akt, and in VHL-deficient renal cell carcinoma xenografts (20,39). Consistent with the findings here in spontaneously arising hamartomas in LKB1ϩ/Ϫ mice, recent studies using human glioblastoma xenografts and transplanted murine breast carcinomas also found rapamycinsensitivity of FDG-PET imaging of these tumors (50,51). Data from LKB1 and AMPK-deficient MEFs demonstrate that HIF-1␣ and HIF-1␣ targets are dramatically up-regulated in these cells under normoxic conditions, indicating that HIF-1␣ up-regulation is not a secondary consequence of other tumor mutations or hypoxia present within the hamartomas.…”
Section: Discussionsupporting
confidence: 79%
“…HIF-1␣ has been shown to be an excellent correlate of rapamycin response in a transgenic model of prostate neoplasia dependent on activated Akt, and in VHL-deficient renal cell carcinoma xenografts (20,39). Consistent with the findings here in spontaneously arising hamartomas in LKB1ϩ/Ϫ mice, recent studies using human glioblastoma xenografts and transplanted murine breast carcinomas also found rapamycinsensitivity of FDG-PET imaging of these tumors (50,51). Data from LKB1 and AMPK-deficient MEFs demonstrate that HIF-1␣ and HIF-1␣ targets are dramatically up-regulated in these cells under normoxic conditions, indicating that HIF-1␣ up-regulation is not a secondary consequence of other tumor mutations or hypoxia present within the hamartomas.…”
Section: Discussionsupporting
confidence: 79%
“…[25][26][27][28][29] In particular, five MMTV-c-Neu mice bearing tumors were treated with 150 g rapamycin (a dose approximately 3 times higher than the dose used in our study) for 32 days and tumor regression was observed. 29 However, the effect of rapamycin on longevity of cancer-prone mice has not been previously investigated.…”
Section: Discussionmentioning
confidence: 90%
“…29 Second, consistent with indirect mechanism of action, rapamycin inhibited cancer growth in mice more profoundly than in cell culture. 27,31 And third, similar to CR, rapamycin extends lifespan in a heterogeneous group of mice, which die from various diseases not necessarily related to cancer.…”
Section: Discussionmentioning
confidence: 98%
“…42). In these mice, an early transient increase in apoptosis was observed in tumor cells after 3 h of rapamycin treatment but not after 7 days.…”
Section: Discussionmentioning
confidence: 99%